STRATEGI PENGEMBANGAN PENDAMPINGAN SEKOLAH LAPANG PENGELOLAAN TANAMAN TERPADU (SL-PTT) PADI SAWAH DI BANGKA BELITUNG - IRMA AUDIAH FACHRISTA; RISFAHERI RISFAHERI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2013)
Integrated Crops Management Field School (ICM-FS) of Paddy is a strategic programfrom Ministry of Agriculture. ICM-FS is designed to accelerate ICM to the farmer. ICM-FS has been held at Bangka Belitung since 2009. Some of strategic are needed to be formulate, in order to develop this program. The experiment was conducted in March - August 2011. The location of this experiment was choosen purposively at South Bangka and Central Bangka. The experiment was conducted with the survey approach. Respondents were selected by purposive random sampling consisting of ICM-FS participating farmers, farmer cooperators, agricultural extension and related agencies.